KEMAMPUAN KERJA DAN KEPUASAN KERJA PENGARUHNYA TERHADAP KINERJA KARYAWAN DEPARTEMEN BAGGAGE SERVICE PT. GAPURA ANGKASA CABANG DENPASAR - Gumi, Wiryawan Suputra; Juniasih, Ida Ayu Komang; Da Cruz, Maria Yosefa Lopes (JUIMA : JURNAL ILMU MANAJEMEN, 2019)
This study aims to determine the effect of work ability and job satisfaction on employee performance at the Baggage Service Department of PT Gapura Angkasa Denpasar Branch. The number ofsamplesis 41 respondents who are employees of PT.Gapura Angkasa Denpasar Branch. Data analysis techniques used are the validity test, reliability test, classic assumption test, multiple regression analysis, and hypothesis testing. Regression equation results: Y = 6.210 + 0.391X1 + 0.310X2, so it can be concluded that work ability and job satisfaction have a positive effect on employee performance. Hypothesis test results prove that work ability and job satisfaction significantly influence employee performance.